The circadian rest‐activity patterns in mild‐moderate Alzheimer's disease patients. (31st December 2021) - Targa, Adriano; Benitez, Ivan David; Dakterzada, Faride; Araujo, John Fontenele; Minguez, Olga; Huerto, Raquel; Tahan, Nuria; Barbe, Ferran; Piñol‐Ripoll, Gerard
Abstract: Background: Alterations in the circadian rhythms are present in the presymptomatic phase of Alzheimer's disease (AD), possibly contributing to its pathogenesis. However, it is unknown whether such alterations could be associated with worse outcomes once the individuals are diagnosed with the disease. We aimed to evaluate the association between the rest‐activity rhythm and AD‐related outcomes in patients with mild‐moderate AD. Method: The cohort included 100 individuals with mild‐moderate AD. The rest‐activity rhythm was assessed through the use of actigraphy for 14 days. Cerebrospinal fluid was obtained to determine the levels of distinct pathological markers of the disease and neuropsychological evaluation was carried out at the beginning of the study and after 12 months of follow‐up. Result: We observed that older age was associated with increased fragmentation of the rest‐activity rhythm (per 1 SD increase, change [SD] of 0.311 [0.096]; p = 0.002) whist female sex was related to higher synchronization between the endogenous rhythm and the zeitgebers (per 1 SD increase, change [SD] of 0.780 [0.193]; p < 0.001). The rest‐activity rhythm was also associated with disease‐related outcomes. Accordingly, there was an association between higher NF‐L levels an increased relative amplitude (per 1 SD increase, change [95% CI] of 240.480 [59.176 to 421.784]; p = 0.010). In addition, increased fragmentation of the rhythm at the baseline was associated with enhanced cognitive decline after one year of follow‐up independently of age, sex, ApoE4 status, educational level, and pharmacological treatment (per 1 SD increase, change [95% CI] of ‐0.576 [‐1.148 to ‐0.005]; p = 0.048). Conclusion: Our results suggest a potential role for the rest‐activity rhythm in predicting both molecular and clinical outcomes in patients with mild‐moderate AD. Further studies are warranted to confirm these findings and to elucidate whether there is causality among the observed associations. In case of a positive response, the circadian rest‐activity rhythm could be a promising target to prevent the cognitive decline.